2015
DOI: 10.1016/j.chb.2014.11.073
|View full text |Cite
|
Sign up to set email alerts
|

The role of regulation in medical student learning in small groups: Regulating oneself and others’ learning and emotions

Abstract: This study examines the role of regulatory processes in medical students as they learn to deliver bad news to patients in the context of an international web-based problem based learning environment (PBL). In the PBL a medical facilitator and students work together to examine video cases on giving bad news and share their perspectives on what was done effectively and what could be done differently. We examine how regulation occurs within this collaboration. A synchronous computer-supported collaborative learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 56 publications
3
39
0
9
Order By: Relevance
“…As such, the sample is representative among studies with similar expert participants (Doleck et al 2015;Duffy et al 2015;Lajoie et al 2015;Naismith 2013). A second limitation of the current work was with regard to how emotions were measured.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the sample is representative among studies with similar expert participants (Doleck et al 2015;Duffy et al 2015;Lajoie et al 2015;Naismith 2013). A second limitation of the current work was with regard to how emotions were measured.…”
Section: Discussionmentioning
confidence: 99%
“…Questions as well as metacognitive statements trigger the discussion for knowledge construction. Lajoie et al (2015) demonstrated that metacognitive activity improved as the group discourse increased. Questioning plays an important role within the process of collaborative knowledge building.…”
Section: Discourse Moves Supporting Collaborative Knowledge Buildingmentioning
confidence: 99%
“…Each learner, can bring different self-regulatory expertise to improve his/her self-and co-learning by sharing the cognitive demands of the task leading to coregulation. Co-regulation assumes that the social group can ease the metacognitive and cognitive demands for each individual through the sharing of monitoring and regulating task processes (Lajoie et al 2015;Hadwin and Oshige 2011;Lajoie and Lu 2012). Although the ultimate objective of co-regulation is to improve self-regulation there is a need to focus on learners' mutual regulatory activity during problem solving session to understand how members engage in productive collaborative learning.…”
mentioning
confidence: 99%
“…As questões do questionário incluíram percepção do ambiente de aprendizagem, crenças de auto eficácia, efeito positivo de estudo, apoio social, indicadores de aprendizagem autorregulada, e desempenho acadêmico (avaliado por meio de testes de progresso). Lajoie et al (2015), com objetivo de examinar a relação entre a metacognição e as atividades de um grupo de PBL, descreveram os resultados de duas sessões projetadas para ajudar a quatro estudantes de medicina (2 do Canadá, 2 de Hong Kong) a entender os princípios da condução de uma entrevista médica para dar más notícias ao paciente. O ambiente de instrução consistiu de cinco módulos online por meio do software de conferência web Adobe Connect 9.…”
Section: Resultsunclassified